Noise is Not Volume Alone – Ambiences and Drony Experiments in Music and Sound Art - Luna, Ianni Barros (Revista Vórtex, 2021)
Noise is a complex category that has been used to describe instances of disturbance and disruption in technical vocabulary and in many artistic languages. In music, and more precisely, in sound art, noise has been imbued with specific significations that operate as aesthetical signifiers that convey meaning even beyond its intensity of volume. In this article, the theoretical aspects of noise are articulated through the analysis of concerning discourse around the transformations of the concept of sound, which ultimately resulted in the designation of a genre in itself – noise. Furthermore, it is through the enhancement of a "˜sonic turn' that the notion of listening as a generative aesthetic practice has referred to the body as the main instance of meaning construction in relation to both time and space.